Fusing international business and marketing: A bibliometric study - Lázaro Florido-Benítez; Ignacio Aldeanueva Fernández (Administrative Sciences, 2022)
This study aimed to provide an assessment of marketing on international business and to organize and classify the literature on marketing in order to clarify the importance of this tool and encourage future research in the projection of international business marketing (IBM) and the power of the ubiquity of this tool in the hands of the users. It is a bibliometric study, and this work focused on international business and marketing articles published in major international marketing, expansion, strategies, and business journals from 2000 to 2020; this topic is scattered across various journals and second data in many disciplines. The investigation reviewed and collected data on the specific paradigm of research that discusses, investigates, and evaluates the topic of IBM. The results showed a new paradigm applied to the topic of IBM and classified it into four first-order research streams: academic research, international business, international development strategies, and customers. The contribution of this study is important in order to identify new challenges and opportunities for marketers, researchers and international companies and in terms of disentangling existing contradictions, applying a new theoretical framework to make better future decisions by large companies, and providing a higher quality to new research in the context of IBM.
Keywords: 350; authors; bibliometric; disciplines; international business marketing; internationalization; universities